“Determinación de la viabilidad de semilla de sacha inchi (plukenetia volubilis L.) en vivero. Accesión pinto recodo, bajo seis formas de conservación” - Garcia Chujutalli, Lucas (2015)
The culture of sacha inchi (Plukenetia volubilis l.) is a euphorbiacea which commonly known as mani of monte, sacha peanut or Inca-peanut. In recent years its importance has increased markedly from an economic and industrial point of view especially on the international market, given its high content, mainly proteins, amino acids, essential fatty acids (Omega 3, 6, and 9) and vitamin E (tocopherols and tocotrienols), with respect to the seed of other oilseeds (peanut, Palm, soybean, and sunflower) (Penguin, 2005). In the Peru lies to the sacha inchi, in the wild in different places of San Martin, Amazonas, Ucayali, Madre de Dios and Loreto. San Martin is located in the entire basin of the Huallaga, in the province of Lamas, in the Valley of the Armhole, upper and under may grow from 100 to 2000 meters (valleys 1991). Thanks to the studies being made by INRA and the llAP has been to identify promising genetic materials...